91.5k views
4 votes
Solve the system of equations by elimination.

2x - y + 3z=-1
x + 2y - 4z=-1
y – 2z=0

1 Answer

4 votes

Answer:

x = -1, y = 2 and z = 1

Explanation:

The given system of equations are :

2x - y + 3z= -1 ....(1)

x + 2y - 4z = -1 ......(2)

y – 2z = 0 .....(3)

Equation (3) can be written as :

y = 2z

Use y = 2z in equation (2)

x + 2(2z) - 4z = -1

x + 4z - 4z = -1

x = -1

Put the value of x in equation (1) :

-2 -y +3z = -1

-y+3z = 1 ....(4)

Adding equation (3) and (4)

y-2z+(-y+3z)=1

z = 1

Now put z = 1 in equation (4)

-y+3=1

-y = -2

y = 2

Hence, the values of x,y and z are -1, 2 and 1 respectively.

User Myx
by
5.4k points